ENERGY EFFICIENCY: EVALUATION PROBLEMS AND CURRENT SITUATION - DASHKO М.; KRYLOV, V. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
It is studied that today in the context of energy efficiency policy three components dominate - economic development and competitiveness, energy security and climate change prevention. The essence and content of energy efficiency are investigated in the article. The definition of energy efficiency terms used to describe both minor changes, such as the use of energy-saving equipment, and more efficient power plants and energy savings at the level of companies and industries in general, is described. The existing problems are considered and the current state of energy efficiency is analyzed. Analyzed empirical facts show that, for example, Ukrainian consumers and companies spend energy irrationally. In particular, the energy intensity of the Ukrainian economy is 3.8 times higher than in the European Union. The most energy-intensive industries in Ukraine - metallurgy, engineering, chemical and petrochemical (energy saving potential, according to experts in this market is 62-64%), housing and communal services (35-38%), services (5%), agriculture (3-5%). The most energy-intensive industries in Ukraine in 2018, kg of oil equivalent / GDP at purchasing power parity in 2013 prices are given. The goals of energy saving of Ukraine by sectors by 2020 compared to the level of 2005-2009 are indicated. The reasons for the obstacles to the introduction of energy efficiency are substantiated. An assessment of the promotion of energy efficiency, which should include: ensuring unimpeded and full access to information on existing energy efficiency support programs; organization of awareness-raising activities in the field of energy efficiency for the population, authorities, enterprises and financial institutions; conducting trainings for specialists.